PENGUATAN KOMPETENSI PENGELOLA DESA WISATA MELALUI PELATIHAN PELAYANAN PRIMA DI DESA WISATA BANTARAAGUNG - Muhammad Abdul Ghoni; Joel Faruk Sofyan; Arian Zikri; Ina Sawitri; Irman Ramdhan Fauzi (JURNAL ABDIMAS PLJ, 2026)
This Community Service Program (Pengabdian  kepada Masyarakat/PkM) aimed to enhance the  competencies  of  human  resources   managing   the  Bantaragung   Tourism  Village, Majalengka, through service excellence training.  The main problems faced by the partners included limited understanding  of professional tourism services, inadequate communication skills with tourists, and the lack of optimal service orientation toward visitor satisfaction. The implementation  method  employed a  participatory  approach  through  observation,  needs identification, training sessions, service simulations (role play), interactive discussions, and mentoring  activities.  The training  materials  covered  the  concepts  of service  excellence, tourism  service  ethics,   effective  communication,  tourist  complaint  handling,  and  the development  of  professional  attitudes  in  tourism  services.  The  results  of  the  program indicated  improvements in participants’  knowledge, skills, and  awareness  regarding  the importance  of  service  quality  in  supporting  tourism  village  development.  Participants demonstrated   enhanced   communication  skills,  better  service  attitudes,   and  improved understanding  of professional  and  tourist-friendly  service  standards.  The program  also increased  the motivation of tourism village managers  to  consistently implement excellent service  practices  in  daily  tourism  activities.  With  the  improvement of human  resource competencies,   Bantaragung   Tourism  Village   is   expected  to  provide   better   tourism experiences  for  visitors  and  support  the  development  of  competitive  and  sustainable community-based tourism.